On-surface synthesis of nitrogen-doped nanographenes with 5–7 membered rings. Issue 32 (3rd April 2019) - Skidin, Dmitry; Eisenhut, Frank; Richter, Marcus; Nikipar, Seddigheh; Krüger, Justus; Ryndyk, Dmitry A.; Berger, Reinhard; Cuniberti, Gianaurelio; Feng, Xinliang; Moresco, Francesca
Abstract : Nitrogen-doped nanographenes containing five- and seven-membered rings obtained by cyclodehydrogenation on Au(111). Abstract : We report on the formation of nitrogen-doped nanographenes containing five- and seven-membered rings by thermally induced cyclodehydrogenation on the Au(111) surface. Using scanning tunneling microscopy and supported by calculations, we investigated the structure of the precursor and targets, as well as of intermediates. Scanning tunneling spectroscopy shows that the electronic properties of the target nanographenes are strongly influenced by the additional formation of non-hexagonal rings.